Effect of Heartfulness Meditation Practices on Blood Pressure and Quality of Life in Patients with Hypertension – A Randomized Clinical Study - Vijaya Chandra Reddy Konda; Mounica Reddy Pillaram; Visweswara Rao Guthi; Vanajakshamma Velam (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Heartfulness meditation practices are modified form of Raja Yoga and gaining popularity worldwide. Studies have demonstrated the beneficial effects of heartfulness meditation on physical health, psychological health, emotional intelligence, heart rate variability, sleep and even on telomere length. Methods: This is a randomized control study conducted in patients with hypertension to assess the effect of heartfulness meditation practices on blood pressure and quality of life. A total of 112 participants were randomized in 1:1 ratio to either intervention group or control group for a study period of four months. Intervention group were trained on heartfulness meditation practices by certified trainers on three consecutive days and were asked to practice them daily at their home. Quality of life was assessed by MINICHAL scale. Results: After the intervention, there was a significant reduction in mean systolic and diastolic blood pressure in the intervention group compared to baseline (136.71 ± 8.64 vs 130.31 ± 8.78, p <0.001 for systolic BP and 82.78 ± 7.30 vs 77.44 ± 7.55, p <0.001 for diastolic BP). Comparison of BP changes between both the groups after the intervention showed significant reduction in both systolic (p=0.009) and diastolic BP (p=0.002) in the intervention group. There was also a significant improvement in mental domain, somatic domain, and overall quality of life in the intervention group. Conclusion: The four months heartfulness meditation practices resulted in a significant reduction in the mean systolic and diastolic pressures. There was also improvement in the scores related to various aspects of quality of life.